Роль метафоры в формировании иноязычной коммуникативной компетентности у студентов економических специальностей - Гриценко, И.П. (Культура народов Причерноморья, 2014)
Лингвокультурологический подход к выявлению метафорической структуры концептов,
актуальных для сферы делового сотрудничества, позволяет не только понять закономерность
использования, но и прогнозировать возможные идиоматические выражения, используемые в
определенной культуре для описания этого концепта при помощи языковых средств. Установление
подобной взаимосвязи и методические мероприятия, направленные на разработку комплекса
соответствующих упражнений, имеет немаловажное практическое значение для повышения
«концептуальной беглости» в процессе формирования социокультурной компетентности у студентов
экономического профиля. Лінгвокультурологічний підхід до виявлення метафоричної структури концептів, актуальних
для ділової співпраці, дозволяє не лише зрозуміти закономірність використання, але і прогнозувати
можливі ідіоматичні вирази, використовувані в певній культурі для опису цього концепту за допомогою
мовних засобів. Встановлення подібного взаємозв'язку і методичні заходи, спрямовані на розробку
комплексу відповідних вправ, має важливе практичне значення для підвищення "концептуальної
побіжності" у рамках формування іншомовної комунікативної компетентності у студентів
економічного профілю. The relevance of the research results from the necessity to develop socio–cultural competency among
university students as it is believed to be one of the essential requirements for effective international business
cooperation in the increasingly globalised world.
The scientific novelty of the study lies in the attempt to apply the results of lingua–cultural analysis of conceptual
metaphors for the purpose of improving the targeted competency in the process of foreign language acquisition.
The purpose of the article is to reveal the prerequisites for developing socio–cultural component of professional
communicative competency.
To achieve this purpose the following objectives have been set in the research work:
 Define the role of metaphor in conceptual systems of human thought and language taking a conceptual
approach to analysis.
 Specify the way conceptual analysis of metaphor–based idioms can be applied to promote conceptual fluency
of university students.
 Trace the way culturally–based concepts are reflected in everyday language by a wide variety of expressions
on the basis of metaphors «Business is War» and «Office is a Battlefield».
Revealing the metaphorical structure of the most relevant concepts specific for business cooperation provides an
opportunity not only to understand the consistent patterns of idioms used to reflect these concepts in the
particular culture, but to anticipate further idiomatic expressions in terms of the metaphor as well. Detecting
this interrelation can help promote conceptual fluency in the process of communicative competency acquisition
among economics students.